The "Filipino first" policy and the Central Bank, 1958-1961 Island of state strength and economic decolonization - Takagi, Yusuke (Philippine studies : historical and ethnographic viewpoints, 2014)
"A gap exists between the high regard for the Central Bank of the Philippines and the Filipino First policy under Pres. Carlos P. Garcia's administration. Patrimonial interests attempted to exploit the Filipino First policy but relied on the bank for foreign exchange. In such a setting, how could the Central Bank lead economic policy making and become an island of state strength? This article examines this puzzle by analyzing the process that involved politicians, private sector leaders, and even the American government. It argues that the Central Bank supported Filipino First only until it could achieve its policy goal of economic decolonization."